Adsorption of Pb(II) by a polyvinylidene fluoride membrane bearing chelating poly(amino phosphonic acid) and poly(amino carboxylic acid) groups - Xiuli Wang; Pei Liu; Fushun Liu; Xuechun Wang; Min Ji; Laizhou Song (Adsorption Science & Technology)
Pb(II) can cause a hazardous effect on ecosystem and public health due to its high biotoxicity. A polyvinylidene fluoride-type membrane bearing both poly(amino phosphonic acid) and poly(amino carboxylic acid) functional groups was fabricated for the purpose of Pb(II) removal from the aqueous solutions. The adsorption behaviors of the fabricated chelating membrane toward Pb(II) were studied by the series of static and continuous adsorption experiments. When the pH, adsorption equilibrium time, initial Pb(II) concentration, and temperature were 5.1, 300 min, 1.0 mmol g −1 , and 298 K, respectively, Pb(II) uptake of the membrane was 1.1 mmol g −1 . The presence of coexisting metal ions and complexing reagents decreased the Pb(II) uptake. The adsorption kinetic and isotherm adsorption followed pseudo-second-order equation and Langmuir model, respectively; this adsorption process showed a spontaneous and exothermic feature. The bed depth service time and Thomas models were suitable for describing obtained breakthrough curves.